Pivotal role of leptin in insulin effects - Ceddia,R.B. (1998)
The OB protein, also known as leptin, is secreted by adipose tissue, circulates in the blood, probably bound to a family of binding proteins, and acts on central neural networks regulating ingestive behavior and energy balance. The two forms of leptin receptors (long and short forms) have been identified in various peripheral tissues, a fact that makes them possible target sites for a direct action of leptin. It has been shown that the OB protein interferes with insulin secretion from pancreatic islets, reduces insulin-stimulated glucose transport in adipocytes, and increases glucose transport, glycogen synthesis and fatty acid oxidation in skeletal muscle. Under normoglycemic and normoinsulinemic conditions, leptin seems to shift the flux of metabolites from adipose tissue to skeletal muscle. This may function as a peripheral mechanism that helps control body weight and prevents obesity. Data that substantiate this hypothesis are presented in this review.